Studi Pembelajaran Individu pada Perusahaan Publik di Indonesia Identifikasi Variabel Pembelajaran - Salim, Sitti Raha Agoes (Jurnal Aplikasi Manajemen, 2009)
This research to know the learnt individual condition and learning process to individual at public company as learning organization Indonesia. The finding from factor analysis is that the learnt are performed by adaptive, active, and pro-active people. Performed by the learnt individual perspective the individual ability in aspirative, process of clarification, and situational competency.